VORTICAL GRAVITATIONAL FIELDS OF NATURAL AND MANMADE ORIGIN AND THEIR WAVE PROPERTIES - Krylov S.M.; Sobolev G.A. (My University, 1999)
An instrument and results of experiments on dynamical phenomena in gravitation are described. A preliminary interpretation is presented, and some inferences are offered concerning an analogy between dynamic gravitation and electromagnetism, as well as some corollaries from this analogy. The instrument is a radically improved version of the Eotvos torsion balance. It was used to measure variable vortical gravitational fields (also known as relativistic, postnewtonian, or solenoidal fields) of natural origin. A study of their structure revealed that they were generated by processes that are similar to electromagnetic induction. Experiments were made to generate vortical gravitational fields; these experiments succeeded in producing controllable postnewtonian signals and in clarifying some of their features. These experiments with natural and manmade fields were the first to provide reliable evidence of dynamic phenomena really occurring in gravitation. The results of these experiments proved gravitation and electromagnetism to be similar processes, some of the recorded natural vortical gravitational fields showing indications of wave processes similar to electromagnetic ones. One of the likely sources of natural gravitational waves may be earthquakes.